Young adult offending: intersectionality of gender and race - Bell, Kerryn E. (Critical criminology, 2013)
It is an accepted criminological fact that gender and race affect involvement in crime. What has been examined less frequently is the effect of intersectionality of gender and race across the early life course. This research uses Delinquency in a Birth Cohort II: Philadelphia, 1958 to examine the longer term effects on crime of intersectionality during the adolescent and young adult portions of the life course. Findings indicate that intersectionality of gender and race is fundamental for young adults. It is argued that multiracial feminism can best explain why intersectionality must be taken into consideration when looking at offending across the early life course.